Case Report: Meningoencephalomyelitis of Unknown Etiology Manifesting as a Bilateral Cranial Polyneuropathy in 3 Dogs - Levitin, Hilary A.; Lampe, Rachel; Hecht, Silke (Frontiers in Veterinary Science, 2020)
A bilateral cranial polyneuropathy was the primary magnetic resonance imaging (MRI) finding in three medium to large breed dogs diagnosed with meningoencephalomyelitis of unknown etiology. All three dogs presented with a progressive history of vestibular ataxia with either central vestibular or multifocal central nervous system (CNS) neuroanatomical localization. Brain MRI revealed variable degree of bilateral enlargement and/or increased contrast enhancement of the optic, oculomotor, trigeminal, facial, and vestibulocochlear nerves, as well as enhancement of the orbital fissure (oculomotor, trochlear, ophthalmic branch of trigeminal, and abducens nerves). There was evidence of intracranial and cranial cervical meningeal contrast enhancement in all three dogs and of cervical spinal cord lesions in 2. In all cases, more cranial nerves were affected than indicated by neurological examination. Cerebrospinal fluid (CSF) analysis was consistent with a mononuclear pleocytosis in 2 cases and a mixed cell (predominantly lymphocytic) pleocytosis in 1 case. All dogs were treated with immune suppressing medications and showed clinical improvement, although some cranial nerve deficits were persistent at follow up 2 months later. These are the first known cases of MUE diagnosed ante-mortem in a canine population documenting bilaterally symmetrical lesions affecting multiple cranial nerves. While MUE is a common cause of non-infectious inflammatory disease in dogs, it likely encompasses more classifications than have previously been reported, and should remain a differential for dogs of all ages and sizes presenting with cranial nerve deficits.